Electrolyte and lithium ion battery

By adding additive A with a specific structure to the electrolyte of lithium-ion batteries, the problems of SEI film rupture and electrolyte acidity increase due to expansion and contraction of silicon material are solved, and the battery is more efficient circulation and high-temperature storage performance are achieved.

CN119650842AActive Publication Date: 2025-03-18EVE POWER CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411856365.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

During the circulation process, the SEI film ruptures due to the expansion and contraction of the silicon material, which increases the consumption of electrolyte, causing the negative electrode material particles to powder and fall off, and deteriorates the battery's electrical performance. At the same time, the poor thermal stability of fluorovinyl carbonate in the electrolyte leads to an increase in acidity and high gas production, affecting the high-temperature storage performance of the battery.

Method used

A specific additive A is added to the electrolyte. The N atoms connected to the carbonyl group in the pyrimidine ring can bind to the H atoms of HF produced by side reaction of the lithium salt to form a complex, thereby reducing the acidity and gas production of the electrolyte, and forming a uniform and stable interface film on the surface of the positive electrode to reduce cracks in the SEI film.

Benefits of technology

By reducing the acidity and gas production of the electrolyte, reducing the cracks in the SEI film and the irreversible phase change of the positive electrode material, the circulation performance and high-temperature storage performance of lithium-ion batteries are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650842A_ABST
    Figure CN119650842A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte and a lithium ion battery. The electrolyte comprises a lithium salt, an organic solvent and an additive A, in the invention, N atoms, connected with carbonyl, in a pyrimidine ring of the additive A can be combined with H atoms of HF generated by side reaction of lithium salt in the electrolyte to form a complex, so that the effects of reducing the acidity and the gas production rate of the electrolyte are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrolyte and a lithium-ion battery. Background Art

[0002] With the development of society, higher energy density requirements are put forward for lithium-ion batteries. Conventional negative electrode materials can no longer meet the requirements. It is necessary to increase the specific capacity of negative electrode materials by adding silicon. The theoretical specific capacity of silicon is as high as 4200mAh / g, which is a very promising negative electrode material for lithium-ion batteries. However, silicon expands and shrinks by more than 300% in a fully lithium-embedded state, which easily causes the solid electrolyte interface (SEI membrane) to rupture. During the battery cycle, the SEI membrane is constantly regenerated and ruptured, thereby accelerating the consumption of electrolyte, causing the negative electrode material particles to pulverize and fall off, and deteriorating the battery's electrical performance. In order to alleviate this situation, fluoroethylene carbonate (FEC) is often added to the electrolyte, but FEC has poor thermal stability and will react with LiPF6, ethylene carbonate (EC), etc. at high temperatures, resulting in increased electrolyte acidity and high gas production, which deteriorates the high-temperature storage performance of the battery. Summary of the invention

[0003] The embodiments of the present invention provide an electrolyte and a lithium-ion battery, which can improve the problems of increased acidity of the electrolyte and high gas production.

[0004] In a first aspect, an embodiment of the present invention provides an electrolyte, comprising a lithium salt, an organic solvent and an additive A, wherein the additive A has a structural formula of

[0005]

[0006] , wherein R1 and R2 independently include hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, isocyanate, sulfonyl, acyl which is unsubstituted or substituted by a second substituent, C1-C4 olefin which is unsubstituted or substituted by a second substituent, C1-C4 alkyl which is unsubstituted or substituted by a second substituent, C3-C4 cycloalkyl which is unsubstituted or substituted by a second substituent, C1-C4 alkoxy which is unsubstituted or substituted by a second substituent, One or more of an aryl group having 5 to 18 ring atoms substituted by a substituent, a heteroaryl group having 5 to 18 ring atoms which is unsubstituted or substituted by a second substituent, an aryloxy group having 5 to 18 ring atoms which is unsubstituted or substituted by a second substituent, and a heteroaryloxy group having 5 to 18 ring atoms which is unsubstituted or substituted by a second substituent, wherein the second substituent comprises one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, acyl, sulfonyl, C1-C4 alkyl, and C1-C4 alkoxy.

[0007] In one embodiment, the mass content of the additive A in the electrolyte is 0.1% to 1.0%; and / or

[0008] The lithium salt comprises one or more of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide; and / or

[0009] The concentration of the lithium salt in the electrolyte is 1.0 mol / L to 1.3 mol / L.

[0010] In one embodiment, the electrolyte further includes vinylene carbonate, and the mass content of the vinylene carbonate in the electrolyte is 0.2%-1.0%.

[0011] In one embodiment, the electrolyte further includes fluoroethylene carbonate, and the mass content of the fluoroethylene carbonate in the electrolyte is 4%-12%.

[0012] In one embodiment, the electrolyte further includes a lithium salt additive.

[0013] In one embodiment, the lithium salt additive includes one or more of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium bis(oxalatoborate), and lithium difluorobis(oxalatophosphate); and / or

[0014] The mass content of the lithium salt additive in the electrolyte is 0.5% to 1.0%.

[0015] In one embodiment, the electrolyte further includes a sulfur-containing additive.

[0016] In one embodiment, the sulfur-containing additive includes one or more of 1,3-propane sultone, sulfur and triallylamine copolymer, vinyl sulfate, and methylene methane disulfonate; and / or

[0017] The mass content of the sulfur-containing additive in the electrolyte is 0.5-1.0%.

[0018] In a second aspect, an embodiment of the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and the above-mentioned electrolyte.

[0019] In one embodiment, the negative electrode plate includes a current collector and a negative electrode active material disposed on the current collector, and the negative electrode active material includes graphite and silicon-carbon material; and / or

[0020] The positive electrode plate includes a current collector and a positive electrode active material disposed on the current collector, wherein the positive electrode active material includes a nickel-cobalt-manganese ternary material, and the chemical formula of the nickel-cobalt-manganese ternary material is Li(Ni x Co y Mn z )O2, where x≥0.8, 0 <y≤0.2,0<z≤0.2,x+y+z=1

[0021] Beneficial effects of the embodiments of the present invention:

[0022] In the embodiment of the present invention, the N atom connected to the carbonyl group in the pyrimidine ring of the additive A can combine with the H atom of HF produced by the side reaction of the lithium salt in the electrolyte to form a complex, thereby achieving the effect of reducing the acidity of the electrolyte and the gas production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 is the structural formula of additive A provided in this application;

[0025] Figure 2 is the structural formula of Additive A provided in Example 1 of the present application;

[0026] Figure 3 is the structural formula of Additive A provided in Example 2 of the present application;

[0027] Figure 4 It is the structural formula of Additive A provided in Example 3 of the present application. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. In addition, in the description of the present application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as indicators and do not impose numerical requirements or establish an order.

[0030] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0031] The technical solution of this application is as follows:

[0032] In a first aspect, an embodiment of the present application provides an electrolyte, comprising a lithium salt, an organic solvent and an additive A, wherein the additive A has a structural formula of

[0033]

[0034] , wherein R1 and R2 independently include hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, isocyanate, sulfonyl, acyl which is unsubstituted or substituted by a second substituent, C1-C4 alkene which is unsubstituted or substituted by a second substituent, C1-C4 alkyl which is unsubstituted or substituted by a second substituent, C3-C4 cycloalkyl which is unsubstituted or substituted by a second substituent, C1-C4 alkoxy which is unsubstituted or substituted by a second substituent, The invention can be selected from the group consisting of an aryl group having 5 to 18 ring atoms substituted by a substituent, a heteroaryl group having 5 to 18 ring atoms which is unsubstituted or substituted by a second substituent, an aryloxy group having 5 to 18 ring atoms which is unsubstituted or substituted by a second substituent, and a heteroaryloxy group having 5 to 18 ring atoms which is unsubstituted or substituted by a second substituent, wherein the second substituent can include one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, acyl, sulfonyl, C1-C4 alkyl, and C1-C4 alkoxy.

[0035] In the present application, the N atom connected to the carbonyl group in the pyrimidine ring of additive A has a lone pair of electrons. Since the lone pair of electrons of the N atom does not participate in conjugation, it can combine with the H atom of HF produced by the side reaction of the lithium salt in the electrolyte to form a complex, thereby reducing the content of HF produced by the side reaction of the lithium salt in the electrolyte, thereby achieving the effect of reducing the acidity and gas production of the electrolyte, and improving the high-temperature stability of the electrolyte; the anhydride group in additive A can form a uniform and stable interface film on the surface of the positive electrode, thereby effectively reducing the generation of cracks in the SEI film, and reducing the irreversible phase change of the positive electrode material, thereby improving the comprehensive performance of the lithium-ion battery.

[0036] In some embodiments, R1 and R2 are independently one of an alkyl group, a fluorine atom, a fluoroalkyl group, a vinyl group, a propenyl group, an acetyl group, a fluoroacetyl group, a methanesulfonyl group, an isocyanate group, and a cyano group.

[0037] In some embodiments, the mass content of the additive A in the electrolyte is 0.1% to 1.0%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc. In this way, the comprehensive performance of the lithium-ion battery can be effectively improved.

[0038] In some embodiments, the electrolyte further includes vinylene carbonate (VC).

[0039] In some embodiments, the mass content of vinylene carbonate in the electrolyte is 0.2%-1.0%, for example, it can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc. In this way, the formation of a dense SEI film at the negative electrode of the battery can be promoted, while the impedance of the negative electrode can be controlled. VC forms a film at the negative electrode of the battery. If the amount of VC added is too little, the density of the SEI film formed at the negative electrode is low. If the amount added is too large, the impedance of the negative electrode will increase and cause gas production. By adding additive A to the electrolyte, the problem of high gas production caused by VC can be alleviated.

[0040] In some embodiments, the electrolyte further includes fluoroethylene carbonate (FEC).

[0041] In the present application, when the negative electrode material of the battery contains silicon material, due to the high expansion and contraction of silicon, the negative electrode material particles are easily pulverized and fall off. FEC can form a film on the negative electrode of the battery, thereby slowing down the damage to the SEI film caused by the expansion and contraction of the silicon material. However, FEC will react with LiPF6, EC, etc. at high temperatures, resulting in increased acidity of the electrolyte and high gas production. The problems of high electrolyte acidity and high gas production caused by FEC can be alleviated by adding additive A.

[0042] In some embodiments, the mass content of the fluoroethylene carbonate in the electrolyte is 4%-12%. In this way, the damage of the negative electrode material silicon to the SEI film can be slowed down, while ensuring the high temperature storage performance and cycle performance of the battery. Too much FEC addition will deteriorate the high temperature storage performance of the battery, and too little FEC addition will deteriorate the cycle performance of the battery.

[0043] In some embodiments, the electrolyte further includes a lithium salt additive, so as to reduce the internal resistance of the battery and improve the high temperature storage performance of the battery.

[0044] In some embodiments, the lithium salt additive includes one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO2F2), lithium bis(oxalatoborate) (LiBOB), and lithium difluorobis(oxalatophosphate) (LiODFP).

[0045] In some embodiments, the mass content of the lithium salt additive in the electrolyte is 0.5% to 1.0%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc.

[0046] In some embodiments, the electrolyte further includes a sulfur-containing additive. In the present application, the sulfur-containing additive can assist film formation at the positive and negative electrodes of the battery and has high thermal stability.

[0047] In some embodiments, the sulfur-containing additive includes one or more of 1,3-propane sultone (PS), sulfur and triallylamine copolymer (PST), dithiodiethyl sulfate (DTD), and methylene methane disulfonate (MMDS).

[0048] In some embodiments, the mass content of the sulfur-containing additive in the electrolyte is 0.5-1.0%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc. In this way, a dense SEI film can be formed at the negative electrode of the battery, and the cycle performance of the battery can be guaranteed. If the amount of sulfur-containing additive added is too small, the density of the SEI film of the negative electrode is low, and if the amount is too large, the negative electrode will be over-filmed, resulting in a decrease in the battery cycle performance.

[0049] In some embodiments, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI).

[0050] In some embodiments, the concentration of the lithium salt in the electrolyte is 1.0 mol / L to 1.3 mol / L, for example, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, etc.

[0051] In some embodiments, the organic solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0052] In some embodiments, the organic solvent includes ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate, and the volume ratio of the ethylene carbonate, the propylene carbonate, the dimethyl carbonate, the diethyl carbonate and the ethyl methyl carbonate is (20-40): (0-20): (0-20): (5-20): (30-50).

[0053] The embodiment of the present application also provides a lithium-ion battery, comprising a positive electrode plate, a negative electrode plate and the above-mentioned electrolyte.

[0054] In some embodiments, the negative electrode plate includes a current collector and a negative electrode active material disposed on the current collector, and the negative electrode active material includes graphite and silicon-carbon material.

[0055] In some embodiments, the gram capacity of the negative electrode active material is ≥450 mAh / g. In this way, the negative electrode active material has a higher gram capacity, that is, the silicon content in the negative electrode active material is higher, and by adding additive A to the electrolyte, the high temperature cycle performance and storage performance of the battery can be effectively improved.

[0056] In some embodiments, the positive electrode plate includes a current collector and a positive active material disposed on the current collector. The positive active material includes a nickel-cobalt-manganese ternary material, and the chemical formula of the nickel-cobalt-manganese ternary material is Li(Ni x Co y Mn z )O2, where x≥0.8, 0<y≤0.2, 0<z≤0.2, and x + y + z = 1. Thus, since the nickel-cobalt-manganese ternary material has a higher specific capacity, the capacity of the positive active material can be improved. At the same time, due to the strong oxidizing property of the nickel-containing positive electrode, by adding additive A to the electrolyte, a uniform and stable interfacial film can be promoted to form on the positive electrode surface, alleviating the oxidation of the electrolyte at the positive electrode, reducing the dissolution of the transition metal of the positive electrode, and thus improving the storage performance of the battery.

[0057] The present application will be specifically described below through specific embodiments. The following embodiments are only partial embodiments of the present application and do not limit the present application. The raw materials used in the following embodiments are all commercially available products unless otherwise specified.

[0058] Example 1

[0059] An electrolyte and its preparation method include the following steps:

[0060] (1) Mix ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate at a volume percentage of 20%:20%:60% to obtain an organic solvent;

[0061] (2) Under an argon atmosphere, add vinylene carbonate (VC), fluoroethylene carbonate (FEC), lithium difluorophosphate (LiPO2F2), 1,3-propane sultone (PS), and additive A (3-[2-amino-4,6-dimethylpyrimidine] maleic anhydride, the structural formula is as attached Figure 2 shown) to the organic solvent, and then add lithium hexafluorophosphate, and stir and mix at a temperature of 10°C to obtain an electrolyte;

[0062] Among them, the mass fraction of vinylene carbonate in the electrolyte is 0.5%, the mass fraction of fluoroethylene carbonate in the electrolyte is 8%, the mass fraction of lithium difluorophosphate in the electrolyte is 1.0%, the mass fraction of 1,3-propane sultone in the electrolyte is 0.5%, the mass fraction of 3-[2-amino-4,6-dimethylpyrimidine] maleic anhydride in the electrolyte is 0.3%, and the concentration of lithium hexafluorophosphate in the electrolyte is 1.0 mol / L.

[0063] A lithium-ion battery and its preparation method include the following steps:

[0064] (1) preparing a negative electrode material (including graphite, silicon carbon, with a gram capacity of 450 mAh / g), a conductive agent (acetylene black) and a binder (CMC and SBR with a mass ratio of 2:3) into a slurry in a mass percentage of 94:1:2:3, coating the slurry on a copper foil current collector, and vacuum drying to obtain a negative electrode sheet;

[0065] (2) preparing a slurry of positive electrode material NCM811, conductive agent (acetylene black) and binder (PVDF) in a mass ratio of 94:3:3, coating the slurry on an aluminum foil current collector, and vacuum drying to obtain a positive electrode sheet;

[0066] (3) Assemble the positive electrode sheet, the negative electrode sheet, the Celgard 2400 separator and the above-mentioned electrolyte into a soft-pack battery.

[0067] Example 2

[0068] This embodiment is basically the same as embodiment 1, except that the additive A in this embodiment is 3-[2-amino-4,6-trifluoromethylpyrimidine] maleic anhydride (structural formula as shown in the attached figure). Figure 3 shown).

[0069] Example 3

[0070] This embodiment is basically the same as embodiment 1, except that the additive A in this embodiment is 3-[2-amino-4,6-dimethylsulfonyl] maleic anhydride (structural formula as shown in the attached figure). Figure 4 shown).

[0071] Example 4

[0072] This embodiment is substantially the same as Embodiment 1, except that the mass fraction of additive A in the electrolyte is 0.1% in this embodiment.

[0073] Example 5

[0074] This embodiment is substantially the same as Embodiment 1, except that the mass fraction of additive A in the electrolyte is 1.0% in this embodiment.

[0075] Example 6

[0076] This embodiment is substantially the same as Embodiment 1, except that the mass fraction of vinylene carbonate in the electrolyte in this embodiment is 0.2%.

[0077] Example 7

[0078] This embodiment is substantially the same as Embodiment 1, except that the mass fraction of vinylene carbonate in the electrolyte in this embodiment is 1.0%.

[0079] Comparative Example 1

[0080] This comparative example is substantially the same as Example 1, except that additive A is not added in this comparative example.

[0081] Comparative Example 2

[0082] This comparative example is substantially the same as Example 1, except that maleic anhydride is used instead of Additive A in this comparative example.

[0083] Comparative Example 3

[0084] This comparative example is substantially the same as Example 1, except that 2-amino-4,6-dimethylpyrimidine is used instead of Additive A in this comparative example.

[0085] Test example:

[0086] The lithium-ion batteries obtained in the examples and comparative examples were electrochemically tested using a Xinwei charge and discharge test cabinet. The test results are shown in Table 1 below.

[0087] (1) Cycle performance test of lithium-ion batteries:

[0088] At 25°C, the lithium-ion battery was charged to 4.2V at 0.5C (nominal capacity) constant current and constant voltage, left for 30 minutes, and then discharged to 2.5V at 1C constant current. The above is one cycle. The lithium-ion battery was charged and discharged 600 times under the above conditions to obtain the capacity retention rate.

[0089] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.

[0090] (2) High temperature storage performance test of lithium-ion batteries:

[0091] At 25°C, the lithium-ion battery was charged at a constant current of 0.5C to a voltage of 4.2V, and then charged at a constant voltage of 4.2V to a current of 0.05C. The volume of the tested lithium-ion battery was V0, and the initial capacity was C0. The lithium-ion battery was then placed in a constant temperature box at 60°C and stored for 90 days, and the volume of the tested lithium-ion battery was taken out and recorded as V1, the capacity remained C1, and the capacity recovered to C2.

[0092] The volume expansion rate (%) of a lithium-ion battery after storage at 60°C for 90 days = (V1-V0) / V0×100%.

[0093] The capacity retention rate (%) of the lithium-ion battery after storage at 60°C for 90 days = (C1 / C0)×100%, and the capacity recovery rate (%) of the lithium-ion battery after storage at 60°C for 90 days = (C2 / C0)×100%.

[0094] (3) Test of HF content in electrolyte:

[0095] The electrolyte was stored at 60°C, and the HF content at 0d (0 day) and 90d (90 days) was measured by ice water titration method, respectively, and recorded as HF-0d and HF-90d.

[0096] Table 1

[0097]

[0098]

[0099] From Table 1 we can see that:

[0100] Compared with Comparative Example 1, the lithium ion battery of the embodiment has a higher capacity retention rate after 600 cycles at 25°C, a lower HF content after 90 days, a lower volume expansion rate after storage at 60°C for 90 days, a higher capacity retention rate after storage at 60°C for 90 days, and a higher capacity recovery rate after storage at 60°C for 90 days. It can be seen that the present application can effectively reduce the acidity, gas production and volume expansion rate of the battery, and improve the capacity retention rate and capacity recovery rate of the battery by adding additive A to the electrolyte.

[0101] Compared with Comparative Examples 2 and 3, the lithium ion battery of the embodiment has a higher capacity retention rate after 600 cycles at 25°C, a lower HF content after 90 days, a lower volume expansion rate after storage at 60°C for 90 days, a higher capacity retention rate after storage at 60°C for 90 days, and a higher capacity recovery rate after storage at 60°C for 90 days. It can be seen that the present application can effectively reduce the acidity, gas production and volume expansion rate of the battery, and improve the capacity retention rate and capacity recovery rate of the battery by adding additive A to the electrolyte compared with maleic anhydride and 2-amino-4,6-dimethylpyrimidine.

[0102] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. An electrolyte, characterized in that: It includes lithium salt, organic solvent and additive A, wherein the structural formula of the additive A is Wherein, R1 and R2 are independently hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, isocyanate, sulfonyl, acyl which is not substituted or substituted by a second substituent, C1-C4 olefin which is not substituted or substituted by a second substituent, C1-C4 alkyl which is not substituted or substituted by a second substituent, C3-C4 cycloalkyl which is not substituted or substituted by a second substituent, C1-C4 alkoxy which is not substituted or substituted by a second substituent, The invention further comprises one or more of an aryl group having 5 to 18 ring atoms substituted by a substituent, a heteroaryl group having 5 to 18 ring atoms which is unsubstituted or substituted by a second substituent, an aryloxy group having 5 to 18 ring atoms which is unsubstituted or substituted by a second substituent, and a heteroaryloxy group having 5 to 18 ring atoms which is unsubstituted or substituted by a second substituent, wherein the second substituent comprises one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, acyl, sulfonyl, C1-C4 alkyl, and C1-C4 alkoxy.

2. The electrolyte according to claim 1, characterized in that: The mass content of the additive A in the electrolyte is 0.1% to 1.0%; and / or The lithium salt comprises one or more of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide; and / or The concentration of the lithium salt in the electrolyte is 1.0 mol / L to 1.3 mol / L.

3. The electrolyte according to claim 1, characterized in that: The electrolyte also includes vinylene carbonate, and the mass content of the vinylene carbonate in the electrolyte is 0.2%-1.0%.

4. The electrolyte according to claim 1, characterized in that: The electrolyte also includes fluoroethylene carbonate, and the mass content of the fluoroethylene carbonate in the electrolyte is 4%-12%.

5. The electrolyte according to claim 1, characterized in that: The electrolyte also includes a lithium salt additive.

6. The electrolyte according to claim 5, characterized in that: The lithium salt additive includes one or more of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium bis(oxalatoborate), and lithium difluorobis(oxalatophosphate); and / or The mass content of the lithium salt additive in the electrolyte is 0.5% to 1.0%.

7. The electrolyte according to claim 1, characterized in that: The electrolyte also includes a sulfur-containing additive.

8. The electrolyte according to claim 7, characterized in that: The sulfur-containing additive includes one or more of 1,3-propane sultone, sulfur and triallylamine copolymer, vinyl sulfate, and methylene methane disulfonate; and / or The mass content of the sulfur-containing additive in the electrolyte is 0.5-1.0%.

9. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and an electrolyte as claimed in any one of claims 1 to 9.

10. The lithium ion battery according to claim 9, characterized in that: The negative electrode plate comprises a current collector and a negative electrode active material disposed on the current collector, wherein the negative electrode active material comprises graphite and silicon-carbon material; and / or The positive electrode plate includes a current collector and a positive electrode active material disposed on the current collector, wherein the positive electrode active material includes a nickel-cobalt-manganese ternary material, and the chemical formula of the nickel-cobalt-manganese ternary material is Li(Ni x Co y Mn z )O2, where x ≥ 0.8, 0 <y≤0.2,0<z≤0.2,x+y+z=1。

Citation Information

Patent Citations

  • Inorganic-organic composite electrolyte membrane, and preparation method and application thereof

    CN113675460A

  • Electrolyte additive, electrolyte and lithium ion battery

    CN118919844A

  • Electrochemical cell with a non-liquid electrolyte

    US20020122980A1